The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s10854-014-2488-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate temperature on ethanol sensing properties of CdO thin films prepared by facile spray pyrolysis method

Abstract: Transparent conducting CdO thin films were deposited on to glass substrates by spray pyrolysis technique. The depositions were carried out at different substrate temperatures with varying film thickness. The effects of substrate temperature on structural, optical and electrical properties of CdO thin films were systematically studied. The CdO films were polycrystalline in nature with cubic crystal structure showing preferential orientation along (111) direction. Wettability results confirmed that the hydrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The negative sign of Hall coefficients for all CdO:In 2 O 3 thin films confirmed the n-type nature conductivity of this system. This is caused due to the existence of defects such as oxygen vacancies and/or intrinsic interstitial cadmium atoms, which can be easily ionized [42,43]. The induced electrons from this process contribute to the conduction of electricity, causing CdO to act as an n-type semiconductor.…”
Section: Hall Effect Measurementsmentioning
confidence: 99%
“…The negative sign of Hall coefficients for all CdO:In 2 O 3 thin films confirmed the n-type nature conductivity of this system. This is caused due to the existence of defects such as oxygen vacancies and/or intrinsic interstitial cadmium atoms, which can be easily ionized [42,43]. The induced electrons from this process contribute to the conduction of electricity, causing CdO to act as an n-type semiconductor.…”
Section: Hall Effect Measurementsmentioning
confidence: 99%
“…The most common application of ethanol sensors is as a breath analyser, since the ethanol vapour in human breath is correlated with the concentration in the blood. Recently, gas sensors based on the semiconducting metal-oxides such as SnO 2 , ZnO, CdO, ITO, WO 3 , and CuO have been found to be very useful for detecting ethanol vapour [1][2][3][4][5][6][7][8][9]. It was found that cadmium oxide based thin films having high sensitivity to ethanol gas because of very thin discontinuous layer surface of CdO films can remarkably enhance its gas-sensing characteristics [10,11].…”
Section: Introductionmentioning
confidence: 99%